BER-delay characteristics analysis of IEEE 802.15.4 wireless sensor networks with cooperative MIMO - Ahmad, Mohd Riduan; Dutkiewicz, Eryk; Huang, Xiaojing (2007)
This paper presents a study of the impact of transmission delay differences between co-operating nodes on bit error rate performance and energy consumption of wireless sensor networks. We consider a wireless sensor network using an Alamouti virtual MIMO (multiple-input multiple-output) configuration between collaborating nodes operating in quasi-static Rayleigh flat-fading channels. Our results show that above certain delay difference (in the range above 0.75Tb), the traditional non-cooperative approach is more energy-efficient than the cooperative strategy and that the transmission delay difference has the most significant on the transmission energy consumption in the delay range of below 0.75Tb.